A drug safety review of treating eosinophilic asthma with monoclonal antibodies. Issue 12 (2nd December 2019) - Mitchell, Patrick; Leigh, Richard
ABSTRACT: Introduction : The last two decades have seen significant progress in the treatment of severe asthma especially the severe eosinophilic phenotype. This review article serves to update the reader on the known safety profiles of these medications. It does not serve as a review of their clinical efficacies. Areas covered : All four of the currently approved monoclonal antibodies (biologics) used in the treatment of severe asthma are discussed with reference to the known safety data garnered from clinical trials and real world evidence. A fifth, approved by The European Commission and FDA, but not yet by NICE or Health Canada, is also discussed. Expert opinion : For each of the five biologics the authors shall summarize the known safety profiles and also the potential adverse effects as their usage is extended long term with suggestions for real world studies to help us develop our knowledge base.